Intellectual Property Rights in the Use of Blockchain Technology From A Contemporary Islamic Legal Perspective - Uti Asikin; Tiza Yaniza; Siti Rohani; Devina Puspita Sari; Sri Widiyastuti (PT Mattawang Mediatama Solution, 2023)
This study investigates the potential of blockchain technology in safeguarding and managing Intellectual Property Rights (IPR) in Indonesia, focusing on copyrights and industrial property rights. It employs a qualitative descriptive methodology, using secondary data from relevant legislation and literature. Data analysis follows the Miles and Huberman technique. The results demonstrate that blockchain technology offers substantial promise in enhancing the protection and administration of IPR. It can validate copyright ownership, record copyright-related transactions, and enhance security and transparency in copyright management. Moreover, it can be relevant in safeguarding trademarks and patents, efficiently tracking ownership and usage, and preventing infringement. The study implies that the implementation of blockchain technology in IPR management in Indonesia requires more detailed regulations and collaboration among stakeholders. It also highlights the need to consider contemporary Islamic Law perspectives to ensure optimal protection for creative and intellectual rights in the digital age.